PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DAN KREATIVITAS GURU TERHADAP PRESTASI BELAJAR SISWA KELAS TINGGI DI SDN MANGUNHARJO 3 KECAMATAN MAYANGAN KOTA PROBOLINGGO - Mimik Supartini (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This research aims to know the influence of instructional media on learning achievement, teachers’ creativity on learning achievement and instructional media and teachers’ creativity simultaneously on learning achievement at SDN Mangunharjo 3 Probolinggo. Ninety (90) students were invoked as respondents in this study. The results show that significant influence of instructional media on learning achievement, teachers’ creativity on learning achievement, and instructional media and teachers’ creativity simultaneously on learning achievement at SDN Mangunharjo 3 Probolinggo.